Princípios da administração pública - a moldura na interpretação das normas de gestão pública e o fundamento para a exclusão do ilícito administrativo por inexigibilidade de conduta diversa - Ferreira, Ana Catarina dos Santos Oliveira (2023)
In a circumstantial analysis that considers and weighs the principles expressly formalized in the caput of art. 37 of the Federal Constitution, as limits to the possibilities of interpretation of the law, in the molds of the Kelsenian theory of the frame of the rule, it is sought to demonstrate that the repressive action of the State, in the scope of administrative sanctioning law, lacks legitimacy when punishing conduct of a public agent that, formally inserted as an administrative illicit act, is shown, among the possibilities of interpretation of the rule and the weighing of values, in line with the constitutional principles of Public Administration. Under the postulates of reasonability and proportionality and in line with the guidelines of the new LINDB, by the provisions of its Article 22, the conduct of the public agent that, under the factual circumstances, observes the values of the Public Administration expressed in the caput of Article 37 of the Federal Constitution, even if formally considered as administrative illicit, should not be sanctioned, since such reprimand goes against the public interest. For this study, the hypothetical-deductive method was used and the legal-interpretative and legal-comparative investigations carried out are eminently theoretical. The theoretical study is supported by bibliographic and documentary research and visits to institutional sites, using as theoretical reference Hans Kelsen, Robert Alexy, Fábio Medina Osório and José Roberto Pimenta Oliveira. The conclusion is that the purpose of the administrative sanction should be, in last analysis, the achievement of public interest, which does not legitimize reprimand to a conduct that is inserted in the frame translated by the principles expressly provided in the caput of Article 37 of the Federal Constitution, as prescribed by article 22 of LINDB.